1993
DOI: 10.1017/s0954579400006234
|View full text |Cite
|
Sign up to set email alerts
|

The double edge of protective and risk factors for delinquency: Interrelations and developmental patterns

Abstract: Protective and risk factors were examined in three samples, each of about 500 boys. Cross-sectional analyses examined a large number of independent variables for their potential protective and risk effects on different levels of seriousness of boys' delinquency. The results showed that protective and risk effects often co-occurred in the same variables, that few variables had risk effects only, and none had protective effects oniy. Protective effects were as likely to promote nondelinquency as to suppress seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
117
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(122 citation statements)
references
References 23 publications
4
117
0
1
Order By: Relevance
“…Moreover, what longitudinal studies have shown is that risk factors rarely, if ever, operate in a social or psychological vacuum. Stouthamer-Loeber et al (1993) have explored the double edge of risk factors for delinquency, and recognize that risk factors have two directional effects. Their argument is that risk factors may not only promote delinquency but also suppress nondelinquency.…”
Section: Delayed Risk and Adult Offendingmentioning
confidence: 99%
“…Moreover, what longitudinal studies have shown is that risk factors rarely, if ever, operate in a social or psychological vacuum. Stouthamer-Loeber et al (1993) have explored the double edge of risk factors for delinquency, and recognize that risk factors have two directional effects. Their argument is that risk factors may not only promote delinquency but also suppress nondelinquency.…”
Section: Delayed Risk and Adult Offendingmentioning
confidence: 99%
“…Although Rutter (1987) has argued that protective factors can only have meaning in the face of adversity, in most studies, protective factors have been defined as simply the positive pole of risk factors (Stouthhamer-Loeber et al, 1993). In this sense, Sameroff (1999) proposed that a better term for the positive end of the risk dimension would be promotive rather than protective factors.…”
Section: Positive Factors For African American Youthmentioning
confidence: 99%
“…Others have emphasized that protective and risk factors are merely opposite ends of the same variable; whether a variable was called a protective or risk factor depended on which end of the continuum was emphasized (Kandel et al, 1988;White, Moffitt, & Silva, 1989). A refinement of this view is the recognition that the protective and risk ends of variables need not be just mirror images of each other but may differ in the magnitude of their relationship to an outcome, that is, the relationship may be nonlinear (Farrington, 1995;Stouthamer-Loeber et al, 1993). Finally, protective factors have been conceptualized as processes that interact with risk factors in reducing the probability of a negative outcome (Rutter, 1985(Rutter, , 1990Rutter, Giller, & Hagell, 1998).…”
mentioning
confidence: 99%
“…To capture this, Stouthamer-Loeber et al (1993) proposed the trichotomization of a distribution that allows for the empirical testing of the relation of different parts of the distribution of an independent variable to the outcome. Participants with a negative score can be compared with those with a neutral score in the middle of the distribution; likewise, participants with a positive score can also be contrasted with those with a neutral score.…”
mentioning
confidence: 99%